Health-Promoting Leadership: Concept, Measurement, and Research Framework - Yao, Lei; Li, Ping; Wildy, Helen (Frontiers in Psychology, 2021)
Employee health is not only positively related to the employee well-being and family happiness, but also impacts upon organizations and society. We searched the health promoting leadership literature in the following database: Web of Science, ProQuest, EBSCO and Chinese local database. We clarify the concept of health promoting leadership, propose a definition of health promoting leadership, and examine measurement scales. We further suggest a research framework for health promoting leadership, demonstrating its potential outcomes(e.g., health, work well-being, life well-being, and psychological well-being), mechanisms which are based on conservation of resources theory, job demands-resources model, social learning theory, and social exchange theory and antecedents (e.g., health values, health awareness, organizational health culture, organizational health climate, and organizational health promotion behavior control). We further identify five potential research areas: research level, performance, the impacts on health promoting leaders themselves, moderators, and research methods.